Violence in Education: A Bibliometric Analysis from Scopus Database - Budianti, Yusnaili; Ruwaidah, Ruwaidah; Megawati, Betti (Jurnal Basicedu, 2023)
This study presents a bibliometric analysis of research on violent education. Using the Scopus database, the study examines research articles containing the term "violence education" in the title that were published globally over a 25-year period from 1998 to 2022. A total of 503 articles were identified, with the United States found to be the most productive country in terms of research on violent education, with 168 publications and the most citations. The study also revealed that research on this topic has been increasing in recent years, peaking in 2022. The analysis also found that "violence," "education," and "intimate partner violence" were the top three keywords related to the topic. The study concludes that preventing violence is an essential aspect of violence education and highlights the importance of ongoing research to develop effective strategies for preventing violence in education and promoting peaceful and safe environments for all